2009
DOI: 10.1103/physreve.80.057102
|View full text |Cite
|
Sign up to set email alerts
|

Temporal structure and gain-loss asymmetry for real and artificial stock indices

Abstract: Previous research has shown that for stock indices, the most likely time until a return of a particular size has been observed is longer for gains than for losses. We demonstrate that this so-called gain-loss asymmetry vanishes if the temporal dependence structure is destroyed by scrambling the time series. We also show that an artificial index constructed by a simple average of a number of individual stocks display gain-loss asymmetry-this allows us to explicitly analyze the dependence between the index const… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…However, empirically one finds that the waiting times of indices are shortest for negative return levels -the opposite of what is to be expected from the long term trend effect. In passing we note that recently it has been found that also single stocks may show some degree of gain-loss asymmetry when the level of return, |ρ|, is getting sufficiently large [21,22]. However, it still remains true that for not too large return levels, e.g.…”
Section: Pacs Numbersmentioning
confidence: 81%
See 1 more Smart Citation
“…However, empirically one finds that the waiting times of indices are shortest for negative return levels -the opposite of what is to be expected from the long term trend effect. In passing we note that recently it has been found that also single stocks may show some degree of gain-loss asymmetry when the level of return, |ρ|, is getting sufficiently large [21,22]. However, it still remains true that for not too large return levels, e.g.…”
Section: Pacs Numbersmentioning
confidence: 81%
“…Recently, the idea of the fear-factor model [24] was reconsidered and generalized by Siven et al [25] by allowing for longer time periods of stock co-movement (correlations). These authors also find that the gain-loss asymmetry is a long timescale phenomena [25], and that it is related to some correlation properties present in the time series [21]. It was also proposed that the gain-loss asymmetry is in close relationship with the asymmetric volatility models (E-GARCH) used by econometricians [26].…”
Section: Pacs Numbersmentioning
confidence: 88%
“…Gains are made in the following days when the asset price readjusts itself to its intrinsic value [36]. It should be mentioned that stochastic volatility models are also successful to explain the leverage effect (see for example [19,25,41]). …”
Section: Discussionmentioning
confidence: 99%
“…It could be attributed for example to the cross-correlations, spanning several days, between the stocks forming the index. As a result, the fear-factor model [14,22] still shows asymmetry after shuffling the returns, however this asymmetry disappears in the generalized asymmetric synchronous market model [19], where the falling stock prices stay synchronized for multiple days.…”
Section: The Shuffled Time-window Methodsmentioning
confidence: 99%
See 1 more Smart Citation